KESELARASAN NILAI PENDIDIKAN AGAMA ISLAM DENGAN KEARIFAN LOKAL DI SD IT AL MA’RUF TEGALREJO MAGELANG - admin; Laili Syarifah (Wahana Islamika: Jurnal Studi Keislaman, 2018)
The focus of this research is the alignment of the value of Islamic religious education with local wisdom at AL MA’RUF Tegalrejo IT Elementary School Magelang, about what, how and opinions of respondents regarding the alignment of the value of Islamic religious education with local wisdom at AL MA’RUF IT Elementary School Tegalrejo Magelang This study used qualitative research, which was conducted at AL MA’RUF Tegalrejo Elementary School. Data collection techniques used were observation, interviews and documentation. In checking the validity of the data, the researcher used source triangulation and the data analysis method used was descriptive method. The author concludes that there is a harmony in the value of Islamic religious education carried out through daily, weekly and annual activities by habituation, learning and example with local wisdom so that students have the following attitudes: 1. The value of faith, including the value of Love to Allah, Cinta Rasul, Faith will be the Last Day. 2. Value of worship, including the value of the discipline of worship, obligatory worship and sunnah, love to read the Qur’an and kalimah thoyyibah. While moral values include values, Tawadhu ', be autonomous, responsibility, and social care.